ANALISIS PENGARUH JUMLAH PENDUDUK DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP KEMISKINAN DI KABUPATEN ROKAN HULU - Tampubolon Ramot; Sari Lapeti; Zuryani Hilmah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine how the influence of Population and Gross Regional Domestic Product on Poverty in Rokan Hulu Regency. The data used in this study is Time Series data for the period 2010-2019. This study uses a comprehensive descriptive analysis method with multiple linear regression using the SPSS 24.0 computer statistical program. The results of the research obtained are the number of population influences poverty and gross regional domestic product does not affect poverty in Rokan Hulu Regency 2010-2019. Total population with a regression coefficient of 0.022 and Gross Regional Domestic Product with a significance coefficient value of 0.224. In the determination test (R2), a value of 0.804 was obtained, which means 80.4% poverty was influenced by the variable Total Population and Gross Regional Domestic Product, while the remaining 19.6% was influenced by other variables not examined in this study.Keywords : total population, regional gross domestic product and poverty